The formation of professional identity and motivation to engage in telecollaboration in foreign language education. Issue 2 (October 2019) - Pfingsthorn, Joanna; Kramer, Christian; Czura, Anna; Stefl, Martin
Abstract : The following article examines the potential of cross-cultural telecollaboration between (student) teachers of foreign languages to contribute to the development of their professional identity. The reported study explores the connection between (student) teachers' conceptualisations of their professional identity and their intrinsic motivation to engage in virtual cooperation with their peers from other countries. The investigation also attempts to assess the potential advantages and challenges for the development of professional identity that (student) teachers associate with telecollaborative efforts in foreign language teacher education. The reported data were collected among 134 student teachers from Poland, the Czech Republic and Germany via pen-and-paper questionnaires including closed-ended items and semantic differential scales. The results indicate a moderate degree of intrinsic motivation to engage in cross-cultural virtual communication with peers, with minor discrepancies between participant groups on various subscales of the construct. Furthermore, the study shows partial correlations between self-reported levels of intrinsic motivation and various professional identity markers that student teachers report, as well as differing degrees of value assigned to cultural and linguistic diversity as a source of professional development. The paper discusses implications of these results for foreign language teacher education policy.